2004
DOI: 10.3748/wjg.v10.i2.200
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor immunopreventive effect in mice induced by DNA vaccine encoding a fusion protein of -fetoprotein and CTLA4

Abstract: AIM:To develop a tumor DNA vaccine encoding a fusion protein of murine AFP and CTLA4, and to study its ability to induce specific CTL response and its protective effect against AFP-producing tumor. METHODS:Murine α-fetoprotein (mAFP) gene was cloned from total RNA of Hepa1-6 cells by RT-PCR. A DNA vaccine was constructed by fusion murine α-fetoprotein gene and extramembrane domain of murine CTLA4 gene. The DNA vaccine was identified by restriction enzyme analysis, sequencing and expression. EL-4 (mAFP) was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Huang et al (2000) reported that even at a relatively high dose of 50 mg of CTLA4-Ig, B-7 molecules remain available to engage with CD28 and thereby provide a signal for T-cell activation. Our present results and those reported previously by other workers on vaccination with Id-CTLA4, DNA encoding CTLA4-Ig, and DNA vaccines fused with CTLA4 provide lines of evidence that CTLA4-Ig at low levels increases both Ab and T-cell proliferation responses (Boyle et al, 1998;Deliyannis et al, 2000;Nayak et al, 2003;Tian et al, 2004). An alternative explain is, under certain circumstances, CTLA4-Ig can augment immunity.…”
Section: J Microbiolsupporting
confidence: 68%
See 1 more Smart Citation
“…Huang et al (2000) reported that even at a relatively high dose of 50 mg of CTLA4-Ig, B-7 molecules remain available to engage with CD28 and thereby provide a signal for T-cell activation. Our present results and those reported previously by other workers on vaccination with Id-CTLA4, DNA encoding CTLA4-Ig, and DNA vaccines fused with CTLA4 provide lines of evidence that CTLA4-Ig at low levels increases both Ab and T-cell proliferation responses (Boyle et al, 1998;Deliyannis et al, 2000;Nayak et al, 2003;Tian et al, 2004). An alternative explain is, under certain circumstances, CTLA4-Ig can augment immunity.…”
Section: J Microbiolsupporting
confidence: 68%
“…In several studies, DNA vaccines harnessing fusion CTLA4 to antigen were exploited for antitumor and antivirus purposes (Boyle et al, 1998;Deliyannis et al, 2000;Nayak et al, 2003;Tian et al, 2004). Our present study sought to assess the efficacy of a novel fusion protein consisting of modified HPV16E7 and the extracellular region of human CTLA4 in the immunotherapy of tumor models expressing HPV16E6E7 protein.…”
mentioning
confidence: 96%
“…A combined DNA vaccine encoding a fusion protein of AFP and CTLA-4 antigen (that binds co-stimulatory B7-1 and B7-2 molecules) obtained both potent specific CTL response and antitumor effect on AFP-producing tumor in mice, without impairing hepatic and renal functions (29). Also uncharacterized and mutated antigens can be targeted with whole tumor cell or tumor lysate-based immunization strategies , as well as using vectors bearing genes making tumor cells immunogenic ; the immune system in these instances shall evolve specificity against these new immunogenic target antigens.…”
Section: Fig 1 Representative Anti-hcc Immunotherapeutic Strategiesmentioning
confidence: 99%